Simulation of Multi Reservoir Operation Rules with Interconnected Tunnel and Water Transfer - Iqbal*, Khairul; Abduh, Moh; Variadi, Variadi (Aceh International Journal of Science and Technology, 2023)
The multi-reservoir operation rules require accuracy in developing its technical parameters. This is done to prevent operational failure in one of the reservoirs. The water transfer concept is to manage the water resources distribution between the receiving watershed and the donor watershed. The availability of transferable water must be prioritized, meeting the water demand of the donor reservoir. Storage capacity in both reservoirs aims to meet water demand, especially in the recipient. The elevation of the interconnecting tunnel is the minimum limit for water use in simulation. The interconnected tunnels' location and capacity will determine the multi-reservoir's operation rule. The interconnected tunnel in the Rukoh Tiro reservoir transfers water in the operation of the two reservoirs. The simulation is carried out in three seasons, considering the inflow of each watershed, the reservoir's downstream water demand, and the reservoir's technical conditions. The simulation results of the Rukoh Tiro reservoir operated simultaneously in all three seasons show that the fulfillment of irrigation water demand can reach 100% as needed. The water transfer process through interconnected tunnels occurs throughout the year. The reservoir operating rule is expected to be a reference in the multi-reservoir operation to obtain an optimal reservoir operating rule.